Inequalities in job-related accessibility: Testing an evaluative approach and its policy relevance in Buenos Aires. (June 2019) - Pucci, Paola; Vecchio, Giovanni; Bocchimuzzi, Lucía; Lanza, Giovanni
Abstract: Accessibility, as a requisite to guarantee the individual ability to participate in valued activities, has been receiving increasing yet scattered attention from diverse theoretical and operational approaches. These approaches focus on how individuals are able to engage in out-of-home activities, participate in social life as well as on their involvement in other activities that contribute to their overall well-being. The paper aims at further investigating such approaches, analysing forms of inequality in job-related mobilities while assuming that a person's accessibility depends on both contextual and individual factors. Taking the Buenos Aires metropolitan area as a suitable testbed, the paper offers an approach to identify the inequalities in job-related accessibility at the neighbourhood scale. The approach considers the relationship between the quality and supply of public transport, level of social exclusion and reachable employment opportunities. The research proposes a synthetic index of inequalities in access to job opportunities (IAO) to identify disadvantaged urban areas characterized by a confluence of problems related to socio-economic deprivations, low accessibility to employment as well as a low mobility and poor quality of transport supply. The approach has an explicit operational dimension and intends to contribute to outlining tailored measures to guarantee better job opportunities, as in the case of people living in areas experiencing sub-standard levels of accessibility to workplaces. Highlights: An approach to assess areas with sub-standard accessibility to job opportunities is proposed. Accessibility provided by transport systems is studied in the light of activity participation. Emerging forms of inequality in job-related mobilities in Buenos Aires are highlighted. The equity effects of current trends transport supply and urban policies are assessed. Policy orientations for disadvantaged areas with emerging mobility needs are proposed.